A comparison of online and offline measures of good-enough processing in garden-path sentences. Issue 2 (7th February 2018) - Qian, Zhiying; Garnsey, Susan; Christianson, Kiel
ABSTRACT: In two self-paced reading and one ERP experiments, this study tested the good-enough processing account, which states that readers sometimes misinterpret sentences like While the man hunted the deer ran into the woods because they fail to fully revise the syntactic structure [Christianson, K., Hollingworth, A., Halliwell, J. F., & Ferreira, F. (2001). Thematic roles assigned along the garden path linger. Cognitive Psychology, 42, 368–407. doi:10.1006/cogp.2001.0752 ]. Such an account predicts more evidence of reanalysis at the disambiguation on correctly- than incorrectly-answered trials. Experiment 1, which asked Did the man hunt the deer? and Experiment 2, which asked Did the sentence explicitly say that the man hunted the deer? showed no difference in reading time between trials with correct and incorrect responses. Experiment 3 found the amplitude of P600 was unrelated to comprehension accuracy. These results converged to suggest that failure to reanalyse ambiguous sentences is not the primary reason for misinterpretation. Three norming studies revealed instead response accuracy was influenced by likelihood of events described in the sentences and questions.